Evaluation of the American college of surgeons thyroid and parathyroid ultrasound course: Results of a web‐based survey. (26th September 2016) - Sharma, Giriraj K.; Sofferman, Robert A.; Armstrong, William B.
Abstract : Objectives/Hypothesis: The American College of Surgeons Thyroid and Parathyroid Ultrasound Skills‐Oriented Course (TPUSC) was designed to teach surgeons how to interpret and perform office‐based head and neck ultrasound (HNUS). The objective of this study was to survey attendees of the TPUSC to evaluate the usefulness of the course, to track surgeon performed HNUS practice patterns, and to help identify potential roadblocks to incorporation of HNUS into a surgeon's practice. Study Design: Cross‐sectional survey. Methods: A Web‐based survey was sent to 952 surgeons who completed the TPUSC between 2010 and 2014. Questions included surgeon specialty, practice type, Likert scale rating of the TPUSC, competency with different HNUS procedures, and current HNUS practice patterns. Results: The response rate was 24%. On a scale from 1 (not useful) to 5 (extremely valuable), the mean course usefulness rating was 4.2. Educational goals were met for 194 (92%) surgeons, and 162 (77%) surgeons reported performing HNUS in their practice. Of 48 surgeons not performing HNUS, 24 (50%) attributed insufficient time in their clinic schedule, and 21 (44%) attributed high equipment costs. Conclusions: The TPUSC is a valuable educational experience for surgeons seeking to gain proficiency in HNUS. The majority of TPUSC graduates gain competency with at least one type of HNUS procedure following the course. Level of Evidence: NA Laryngoscope, 127:1950–1958, 2017